PENGEMBANGAN E-MODUL MATEMATIKA PADA MATERI PECAHAN UNTUK MENDUKUNG PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Sari, Meylinda Ika; Pamungkas, Aan Subhan; Firdaus, Firdaus (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
The aim of this study is to define the development process, feasibility, and describe students' responses to a mathematics e-module on fractions to support differentiated learning in elementary schools. The research was conducted at SD Negeri Pabuaran, Serang District, involving fifth-grade students as the subjects. This study employed the Research and Development (R&D) method through the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The data analysis technique used in this study was descriptive data analysis. The analyzed data include the feasibility analysis of the e-module based on questionnaires completed by media experts, content experts, and students' responses to the e-module. The validation results of the e-module showed that the content experts rated it 3.70, categorized as very good, while media experts rated it 3.29, also categorized as very good. Additionally, the language experts gave a rating of 2.75, categorized as good. This e-module has the potential to make a significant contribution to supporting differentiated learning in elementary school, especially in the mathematics subject.